PUBLIC EQUALITY, DEMOCRACY AND JUSTICE - Ivan Mladenović (Anali Hrvatskog Politološkog Društva, 2015)
This paper examines the principle of public equality which, according to the view Thomas Christiano defends in his book The Constitution of Equality: Democratic Authority and Its Limits, is of central importance for social justice and democracy. Christiano also holds that the authority of democracy, and its limits, are grounded in this principle. Christiano’s democratic theory can be, broadly speaking, divided in two parts. The first part deals with the derivation and justification of the principle of public equality. The second part argues why and how the authority of democracy, and its limits, are based on this principle. This article will deal only with the first part of Christiano’s theory. While I believe that the second part is crucially important for Christiano’s democratic theory, I think that before examining the role of the principle of public equality, it is necessary to examine its nature. For that reason, this paper deals primarily with the nature of the principle of public equality as the requirement of social justice and the basis for the justification of democracy.